PENERAPAN MESIN PERONTOK BIJI JAGUNG BAGI MASYARAKAT PETANI JAGUNG KAMPUNG BIBIOSI KABUPATEN KEEROM - Thomas Pagasis; David Mangallo (Universitas Negeri Makassar, 2026)
The primary challenge in post-harvest corn handling among farmers in Bibiosi Village, Keerom Regency, is the continued use of manual shelling tools, which are time-consuming and labor-intensive, resulting in delayed sales and reduced corn quality. To address this issue, appropriate technology in the form of a gasoline-powered mechanical corn sheller (5.5 HP) was introduced to improve processing efficiency and productivity. The program aimed to increase farmers’ shelling capacity, enhance income, promote technology adoption, and strengthen collaboration among Cenderawasih University, the local community, and the local government. The implementation method included machine fabrication, equipment installation, operational and maintenance training, and evaluation. Performance testing demonstrated that the machine has a production capacity of 350 kg per hour. The application of this technology significantly improves post-harvest efficiency and contributes to increasing farmers’ productivity and welfare. Furthermore, the program fosters technological awareness and encourages a more progressive mindset within the farming community.